Antimicrobial endotoxin‐neutralizing peptides promote keratinocyte migration via P2X7 receptor activation and accelerate wound healing in vivo. (20th July 2018) - Pfalzgraff, Anja; Bárcena‐Varela, Sergio; Heinbockel, Lena; Gutsmann, Thomas; Brandenburg, Klaus; Martinez‐de‐Tejada, Guillermo; Weindl, Günther
Abstract : Background and Purpose: Wound healing is a complex process that is essential to provide skin homeostasis. Infection with pathogenic bacteria such as Staphylococcus aureus can lead to chronic wounds, which are challenging to heal. Previously, we demonstrated that the antimicrobial endotoxin‐neutralizing peptide Pep19‐2.5 promotes artificial wound closure in keratinocytes. Here, we investigated the mechanism of peptide‐induced cell migration and if Pep19‐2.5 accelerates wound closure in vivo . Experimental Approach: Cell migration was examined in HaCaT keratinocytes and P2X7 receptor‐overexpressing HEK293 cells using the wound healing scratch assay. The protein expression of phosphorylated ERK1/2, ATP release, calcium influx and mitochondrial ROS were analysed to characterize Pep19‐2.5‐mediated signalling. For in vivo studies, female BALB/c mice were wounded and infected with methicillin‐resistant S . aureus (MRSA) or left non‐infected and treated topically with Pep19‐2.5 twice daily for 6 days. Key Results: Specific P2X7 receptor antagonists inhibited Pep19‐2.5‐induced cell migration and ERK1/2 phosphorylation in keratinocytes and P2X7 receptor‐transfected HEK293 cells. ATP release was not increased by Pep19‐2.5; however, ATP was required for cell migration. Pep19‐2.5 increased cytosolic calcium and mitochondrial ROS, which were involved in peptide‐induced migration and ERK1/2 phosphorylation. In both non‐infected and MRSA‐infected wounds, the wound diameter was reduced already at day 2 post‐wounding in the Pep19‐2.5‐treated groups compared to vehicle, and remained decreased until day 6. Conclusions and Implications: Our data suggest the potential application of Pep19‐2.5 in the treatment of non‐infected and S . aureus ‐infected wounds and provide insights into the mechanism involved in Pep19‐2.5‐induced wound healing.